Gas explosion characteristics in confined straight and 90 degree bend pipes - Sulaiman, Siti Zubaidah (2015)
Gas explosion inside a pipe is a complex phenomenon. Extensive studies have been carried out to investigate factors governing to the explosion development i.e. the flame speed and the maximum pressure. However, most of the works are limited to open straight pipes. Worst, the effect of the obstructions on the explosion severity is still unclear. Most of the gases used in the industrial piping are highly combustible and has a potential to initiate detonation hazard. In this work, gas explosions inside closed pipes are considered. Experimental and Computational Fluid Dynamic (CFD) analyses using FLACs are adopted to investigate the physical and dynamic behaviour on gas explosion development in pipes. Hydrogen, acetylene, ethylene, propane and methane were used as fuels. The effect of pipe configuration (straight and 90 bend pipe) with different length to diameter ratio (L/D) was investigated. From the results, it was observed that the presence of 90 degree bend enhances the explosion severity by a factor of 1.03-3.58 as compared to that of the straight pipe. Based on the simulation analysis, the compression effect at the bending region and at the end of the pipe plays an important role to attenuate the burning rate, which resulting to a higher flame speeds and hence, increases the overpressure. Interestingly, a maximum overpressure of 14 barg with flame speed of 700 m/s was observed in the smaller pipe of L/D=40 with acetylene fuel which indicated that the detonation-like event take place. The ability of the flame to quench becomes insignificant in a smaller pipe, promoting a strong interaction of the fast flame and turbulence, particularly at the bending. This phenomenon amplifies the mass burning rate, increases the flame speeds and leading to a higher pressure rise. From the results, it shows that fuel reactivity and pipe size and configuration gives a significant effect to the overall overpressure and flame acceleration development which can lead to a catastrophic explosion.